Marketing higher education : understanding how to build and promote the university brand - Koku, Paul Sergius, 1955- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book provides a comprehensive and accessible guide to marketing Higher Education institutions, discussing both how universities are service providers and how education is a service, both of which need to be defined and marketed together. Unlike the current offering available on the subject, this book provides a uniquely applied approach, linking the theory of marketing practice and how it relates to the Higher Education sector through real life case studies and examples. Each topic is covered in depth, including marketing segmentation, pricing, location, brand management, internationalization and expansion. Overarchingly, the book considers how to develop and promote the University as a product and as a brand. Two case studies from real life universities in a broad range of locations are provided at the end of each chapter, alongside questions to aid understanding and application. Holistic and practical, Marketing Higher Education is an ideal guide for academics and students studying services marketing, Higher Education management and leadership, and marketing in the public sector. It will also be an invaluable resource for professionals working in Higher Education administration looking to develop their skills and understanding of marketing and brand building"--
Marketing in universities -- Market segmentation -- Higher education as a product -- Pricing issues -- Location and a university -- Promoting and advertising universities -- Personal selling of a university -- Competition and innovations in higher education -- Names and name change : university brand management -- The eduscape : the university experience -- Internationalization of universities -- The expansion of private universities -- Regulatory issues in higher education.
OCLC-licensed vendor bibliographic record.
Keywords: Universities and colleges -- Marketing; Education, Higher -- Marketing; Branding (Marketing); BUSINESS & ECONOMICS / Marketing / Direct; EDUCATION / Leadership